FRIENDSHIP IN 3 IDIOTS REVIEWED FROM A PSYCHOLINGUISTIC PERSPECTIVE: SYSTEMATIC LITERATURE REVIEW (Lectio: Journal of Language and Language Teaching, 2026)
This study examines the representation of friendship in the film 3 Idiots from a psycholinguistic perspective through a Systematic Literature Review (SLR). Friendship is a fundamental aspect of human social interaction, and language plays a crucial role in shaping cognitive, emotional, and social relationships. Despite the popularity of 3 Idiots as an object of interdisciplinary analysis, studies that specifically explore friendship in the film using a psycholinguistic framework remain limited. This research aims to synthesize existing literature to identify how language use in friendship interactions reflects psycholinguistic processes such as cognition, emotion regulation, and social bonding. The study employed a qualitative SLR approach by systematically searching academic databases, applying inclusion and exclusion criteria, and analyzing selected studies thematically. The findings reveal three dominant themes in the psycholinguistic representation of friendship: cognitive processes in language interaction, emotional expression and affective support, and the social function of language in constructing solidarity and group identity. The dialogues in 3 Idiots demonstrate how language mediates thought, regulates emotions, and reinforces interpersonal bonds among the characters. The results also indicate a significant research gap in integrating psycholinguistic theories with film analysis, particularly in the context of friendship. This study contributes theoretically by extending psycholinguistic inquiry to audiovisual media and relational contexts. Methodologically, it highlights the value of SLR in synthesizing fragmented research across disciplines. Overall, this research provides a comprehensive understanding of how friendship is linguistically and psychologically constructed in film, offering insights for future psycholinguistic and media-based studies.
Keywords: Psycholinguistics; Friendship, 3 Idiots; Film Analysis; Systematic Literature Review